Effects of cold-water immersion compared with other recovery modalities on athletic performance following acute strenuous exercise in physically active participants: a systematic review, meta-analysis, and meta-regression - Moore, E.; Fuller, J. T.; Bellenger, C. R.; Saunders, S.; Halson, S. L.; Broatch, J. R.; Buckley, J. D. (Sports Medicine, 2023)
Background